Application of Geotechnologies in the Characterization of Forage Palm Production Areas in the Brazilian Semiarid Region - Jacqueline Santos de Sousa; Gledson Luiz Pontes de Almeida; Héliton Pandorfi; Marcos Vinícius da Silva; Moemy Gomes de Moraes; Abelardo Antônio de Assunção Montenegro; Thieres George Freire da Silva; Jhon Lennon Bezerra da Silva; Henrique Fonseca Elias de Oliveira; Gabriel Thales Barboza Marinho; Beatriz Silva Santos; Alex Souza Moraes; et al. (AgriEngineering)
Forage scarcity, intensified by climate variability and edaphoclimatic limitations in the Brazilian semiarid region, challenges regional livestock production. In this context, forage palm is a strategic alternative due to its drought resistance and environmental adaptability. However, little is known about the spatial and temporal dynamics of its cultivation. This study aimed to characterize the spatio-temporal dynamics of forage palm cultivation in Capoeiras-PE between 2019 and 2022 using remote sensing data and multitemporal analysis of the Normalized Difference Vegetation Index (NDVI), processed via Google Earth Engine. Experimental areas with Opuntia stricta (“Mexican Elephant Ear”) and Nopalea cochenillifera (“Miúda”) were monitored, with field validation and descriptive statistical analysis. NDVI values ranged from −0.27 to 0.93, influenced by rainfall, cultivar morphology, and seasonal conditions. The “Miúda” cultivar showed a lower coefficient of variation (CV%), indicating greater spectral stability, while “Orelha de Elefante Mexicana” was more sensitive to climate and management, showing a higher CV%. Land use and land cover (LULC) analysis indicated increased sparse vegetation and exposed soil, suggesting intensified anthropogenic activity in the Caatinga biome. Reclassified NDVI enabled spatial estimation of forage palm, despite sensor resolution and spectral similarity with other vegetation. The integrated use of satellite data, field validation, and geoprocessing tools proved effective for agricultural monitoring and territorial planning.